The role of hydrogen in tellurites: crystal structure refinements of juabite, poughite and rodalquilarite - Kampf,A.R.; Mills,S.J. (Journal of Geosciences, 2011)
The crystal structures of the tellurite minerals juabite, CaCu10(Te4+O3)4(AsO4)4(OH)2(H2O)4, poughite, Fe3+2(Te4+O3)2(SO4)(H2O)2·H2O and rodalquilarite, Fe3+2(Te4+O2OH)3(Te4+O3)Cl, have been refined to R1 (Fo > 4sF) = 2.36%, 2.38% and 1.84%, respectively. The determination of H atom positions in all three structures has allowed the elucidation of the hydrogen bonding schemes and detailed bond-valence analyses. These are the only tellurite mineral structures for which H atom positions have been determined. The structures of all contain one-sided Te4+ coordinations as Te4+O3 pyramids with additional anions at greater distances. The one-sided coordinations are attributable to the stereochemically active 6s2 lone-electron-pair of the Te4+. The overall linkage schemes in these structures are quite different, yet all can be considered layer structures in which relatively weak long Te-O and/or Te-Cl bonds are involved in the linkages between layers. In juabite, a long apical Cu-O bond participates in the linkage between layers and, in poughite and rodalquilarite, hydrogen bonding also links the layers.
Keywords: crystal structure; juabite; poughite; rodalquilarite; 6s2 lone-electron-pair; hydrogen bonding